The Urgency of Munasabah the Al-Qur'an and Its Relevance to Verses Related to Educational Values - Hamsah Awing; Achmad Abubakar; Muhammad Yusuf; Nurchamidah; Muhammad Hamsah (al-Afkar, Journal For Islamic Studies, 2024)
Munasabah is a branch of knowledge from the ulumul Qur'an which has an urgent position in the process of interpreting verses. Studying it can provide clarity and astuteness in seeing the relationship between verses, sentences, surahs and the content contained in them. By paying attention to the rules in making munasabah such as paying attention to general. typical, aqli, hissi, cause and effect, similarities and contradictions. However, munasabah is ijtihad, that is, it is only carried out by mufassir who specialize in several branches of knowledge. The consultation process must pay attention to the rules that have been established in order to provide a broader and more detailed understanding. So as to avoid mistakes or exaggerations in interpreting a verse. This research uses a library research approach, while this type of research is based on revelation studies and the technique used is a content analysis technique which aims to review consistency in a text which is described in structured patterns in order to provide scientific and accurate results. The research results show that munasabah on verses and values that lead to education provides comprehensive and detailed explanations in studying every verse, sentence and surah in the Al-Qur’an.